Cell polarity in development and disease - Houston, Douglas W. (Douglas William) (Perspectives on translational cell biology series., 2018)
Cell Polarity in Development and Disease offers insights into the basic molecular mechanisms of common diseases that arise as a result of a loss of ordered organization and intrinsic polarity. Included are diseases affecting highly polarized epithelial tissues in the lung and kidney, as well as loss and gain of cell polarity in the onset and progression of cancer. This book provides a basic resource for understanding the biology of polarity, offering a starting point for those thinking of targeting cell polarity for translational medical research.